Access to Medicines and Distributive Justice: Breaching Doha's Ethical Threshold. Issue 2 (21st April 2014) - Kiddell‐Monroe, Rachel
Abstract The global health crisis in non‐communicable diseases (NCDs) reveals a deep global health inequity that lies at the heart of global justice concerns. Mirroring the HIV/AIDS epidemic, NCDs bring into stark relief once more the human consequences of trade policies that reinforce global inequities in treatment access. Recognising distributive justice issues in access to medicines for their populations, World Trade Organisation (WTO) members confirmed the primacy of access to medicines for all in trade and public health in the landmark Doha Declaration on the TRIPS Agreement and Public Health of 2001.